Participation in early childhood education and care in Finland mitigates the associations between maternal psychological distress and child social and emotional problems at age two - Tervahartiala, Katja; Korja, Riikka; Sarelius, Vilma; Autere, Tuomo-Artturi; Karlsson, Hasse; Carter, Alice S.; Karlsson, Linnea; Nolvi, Saara (Springer Nature, 2026)
It is well-established in previous research that maternal psychological distress may have adverse effects on child social and emotional development. However, less is known about the environmental protective factors on child outcomes. This study aimed to explore the moderating role of Early Childhood Education and Care (ECEC) participation on the associations between maternal long-term prenatal, postnatal or current psychological distress and child social and emotional problems and competence. A total of 1,191 children (Mage = 24.54 months, SD = 0.59; 47.4% girls) were drawn from the FinnBrain Birth Cohort Study in Finland. Children participated either in center-based or family-based ECEC or they were cared for at home. Mothers had filled in self-reports of their long-term psychological distress during pregnancy, and postpartum, and the evaluation of their child social and emotional problems and competence at the child age of 2 years. The results showed that the ECEC participation played a protective role in the relation between current maternal psychological distress and child social and emotional problems. Associations between maternal symptoms and children’s social and emotional problems was attenuated for children who participated in center-based ECEC (β = -0.37, [-0.64, -0.09], p = 0.008), or family-based ECEC (β = -0.75, [-1.11, -0.40], p < 0.001) when compared to children who were cared for at home. This study reinforces our understanding of the ECEC’s potential buffering role in at-risk families and in particular in Nordic countries characterized by high-quality of ECEC and high enrollment rates during early childhood.